Bisnis Model Canvas (BMC) Home Industri Olahan Hasil Laut di Kecamatan Ambunten Kabupaten Sumenep - Rifaq, Isyqi; Lailatul Vitriyah, Nurul (KUBIS, 2024)
Home industries in the food sector, especially in seafood processing, have become an attractive business option for the community in Ambunten District. This research aims to understand the Business Model Canvas (BMC) of Seafood Processing and to identify the SWOT of the Business Model Canvas (BMC) of Seafood Processing in Ambunten District, Sumenep Regency, East Java. The sampling method used is Random Sampling. The results of this research indicate that the Business Model Canvas (BMC) is very helpful in business planning, from sourcing business funding, processing products, to marketing products, and can reduce business failures. Next, the prospects are a more attractive service strategy with seafood products by providing testimonials to consumers, expanding the target market, increasing consumer appeal, and enhancing innovation in seafood product creation.